Anti‐BP180 autoantibody levels at diagnosis correlate with 1‐year mortality rates in patients with bullous pemphigoid. (2nd July 2020) - Monshi, B.; Gulz, L.; Piringer, B.; Wiala, A.; Kivaranovic, D.; Schmidt, M.; Sesti, A.; Heil, T.; Vujic, I.; Posch, C.; Rappersberger, K.
Abstract: Background: Bullous pemphigoid (BP) is the most frequent autoimmune blistering disease mainly affecting elderly patients. Among several published risk factors, a recent post hoc analysis linked anti‐BP180 autoantibodies (AABs) to fatal outcomes in BP. To date, this finding has not been confirmed independently. Objective: To investigate the potential of anti‐BP180‐AAB levels as a marker of prognosis and to identify a cut‐off level indicative of an increased risk for early death. Secondly, to characterize parameters associated with mortality. Methods: Retrospective, single‐centre study of BP patients diagnosed between 2001 and 2012. Analyses included epidemiological and patient‐ and disease‐specific characteristics as well as immunological parameters at diagnosis and during follow‐up. Standardized mortality ratios as well as uni‐ and multivariate regression analyses were calculated. Results: One hundred patients (56 women, 44 men) with a median age of 81 years (interquartile range 74–86) were followed up for a median of 775 days (interquartile range 162–1617). One‐year mortality rates were 25.0% implying a 2.4‐fold increased risk of death compared with the general population. High anti‐BP180 autoantibody levels at diagnosis (CI95 1.30–2.89; P = 0.001), dementia (CI95 1.13–6.72; P =0.03), length of hospitalization (CI95 1.16–2.41; P = 0.01) and age (CI95 1.23–4.19; P = 0.009) correlated significantly with 1‐year mortality. BP180‐AAB concentrations of ≥61 U/mL characterized a subgroup of patients with a particular higher risk for early death compared with the general population (CI95 1.81–3.81; P < 0.0001). Conclusion: In bullous pemphigoid, serum concentrations of BP180 autoantibodies at diagnosis could help to identify patients at risk for death within the first year after diagnosis (cut‐off value 61 U/mL).